Faktor yang Mempengaruhi Holding Period Saham pada Indeks Kompas 100 Tahun 2015-2018 - Yohana Dwi Gita Sirait; Eka Yulianti (Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to determine the effect of Bid-Ask Spread, Market Value, Earning Per Share, and Return On Assets Against Stock Holding Period (Study on Kompas 100 Index Shares Listed on Indonesia Stock Exchange in 2015-2018). The approach of the research method used is quantitative with descriptive and associative methods. The population in this study were 114 companies with a sample of 53 companies in order to obtain 212 observational data. The data analysis technique used is panel data regression analysis. The results of this study indicate that partially the bid-ask spread and market value have a positive effect on the holding period of shares, while the earnings per share and return on assets do not affect the holding period of shares. Simultaneously bid-ask spreads, market value, earnings per share, and return on assets affect the holding period of shares.